Показчик ключових слів тому 34 журналу «Проблеми кріобіології і кріомедицини» - Problems of Cryobiology and Cryomedicine, Editorial Board (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):311–313